DEVELOPMENT OF UMKM AND ITS IMPLICATIONS ON THE POTENTIAL OF CREATIVE ECONOMY-BASED TOURISM IN TOURIST VILLAGE AREAS - Agung Hirmantono (STAI AL-HIDAYAT Lasem, 2023)
Tourism is a trip undertaken by individuals or groups to a place temporarily toseek harmony or balance and happiness in the social, cultural, natural andscientific dimensions. Spillane groups the goals of individual/group travel,including enjoying travel, spending time with family, business matters, andothers. Tourism development is all forms of coordinated activities with the aimof increasing the number of tourists and improving facilities and infrastructureservices, in the form of goods or services and facilities. This is categorized as acomplex activity because this activity coordinates activities, facilities andinfrastructure, objects and attractions, supporting facilities, environmentalfacilities and so on with tourists.